دور الإحالة في اتساق و انسجام الخطاب الشعري قصيدة الحنين لابراهيم ناجي - قعيد, زاوش, نور الهدى مسعودة; عطيه, هنية (Univercty of Eloued, 2020)
تصنف لسانيات النص من أهم الاتجاهات في منظومة البحث اللساني، وقد قامة على فكرة مفادها أن الوحدة اللغوية الكبرى الأساسية في التحليل هي النص وليست الجملة كما كان سائدا من قبل، وترتكز على مبدئين هما الاتساق والانسجام ولعلى الاحالة من أهم الأدوات التي تسهم في اتساق الشامل للنصوص الأدبية على اختلاف أصنافها ومنها الخطاب الشعري. وينصب موضوع دراستنا التي رصدنا فيها أهم العناصر الإحالية الواردة في القصيدة ومدى مساهمتها في تماسك الخطاب الشعري، وجعله كل واحد موحد. Text linguistics is classified as one of the most important trends in the linguistic research system, and it is based on the idea that the main linguistic unit in analysis is the text and not the sentence as it used to be before, and it is based on two principles: consistency and harmony. Literary different types, including poetic discourse. The subject of our study, in which we monitored the most important referral elements contained in the poem, is concerned with the extent of its contribution to the coherence of the poetic discourse, and making it a unified one.
Keywords: الإحالة، الاتساق، الانسجام، الخطاب الشعري; Referral, consistency, harmony, poeticdiscourse